2011
DOI: 10.1055/s-0031-1284240
|View full text |Cite
|
Sign up to set email alerts
|

First Experiences with Simultaneous Skeletal and Soft Tissue Reconstruction of Noma-Related Facial Defects

Abstract: Noma victims suffer from a three-dimensional facial soft-tissue loss. Some may also develop complex viscerocranial defects, due to acute osteitis, chronic exposure, or arrested skeletal growth. Reconstruction has mainly focused on soft tissue so far, whereas skeletal restoration was mostly avoided. After successful microvascular soft tissue free flap reconstruction, we now included skeletal restoration and mandibular ankylosis release into the initial step of complex noma surgery. One free rib graft and parasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We found that the same team would often visit the same site repeatedly and perhaps more importantly, unlike the microsurgical services offered by local surgeons, nearly all of which were performed in major cities, visiting teams concentrated their work in much smaller and much poorer rural areas such as in Sokoto, Nigeria (Noma Children's hospital) and in Malindi, Kenya (Tawfik Hospital and Malindi District Hospital), all of which are located over 700km away from the commercial capital. 5,11,[53][54][55][56][57][58][59][60][61] The study also revealed significant differences in patient selection and flaps performed by visiting surgeons compared to local teams. Noma reconstruction was the primary focus of surgical missions with visiting surgeons performing 94.3% of all noma microsurgical reconstruction in the entire period studied from 1976-2020.…”
Section: Short-term Surgical Missionsmentioning
confidence: 89%
“…We found that the same team would often visit the same site repeatedly and perhaps more importantly, unlike the microsurgical services offered by local surgeons, nearly all of which were performed in major cities, visiting teams concentrated their work in much smaller and much poorer rural areas such as in Sokoto, Nigeria (Noma Children's hospital) and in Malindi, Kenya (Tawfik Hospital and Malindi District Hospital), all of which are located over 700km away from the commercial capital. 5,11,[53][54][55][56][57][58][59][60][61] The study also revealed significant differences in patient selection and flaps performed by visiting surgeons compared to local teams. Noma reconstruction was the primary focus of surgical missions with visiting surgeons performing 94.3% of all noma microsurgical reconstruction in the entire period studied from 1976-2020.…”
Section: Short-term Surgical Missionsmentioning
confidence: 89%
“…6 a–d, necrosis). Often, the necrosis leads to bilateral constriction of temporomandibular joints during the healing period [ 26 ]. Eighty percent of infected children still die because no antibiotics are available.…”
Section: Discussionmentioning
confidence: 99%
“…b The sequelae required multistage reconstruction of bone, soft tissue, and skin. c A free osteocutaneous parascapular flap reconstructed the maxilla (OP Goetz Giessler) [ 26 , 27 ]. d A three-layer nasal reconstruction with a pre-expanded forehead flap and airway opening perfected the reconstruction
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…4 Noma can cause extensive soft tissue losses and trismus; excision of fibrosis and flap replacement are combined with a graded approach to maximize mouth opening, setting the basis for rational application of postoperative physiotherapy. 5 Trismus also may result from soft tissue fibrosis following radiation in head and neck malignancies; the associated chronic radiation dermatitis causes risk of developing skin necrosis, when surgical intervention is needed for restoration of mouth opening. Any of the conditions described above may present a "double trouble" of facial skin loss, real or apparent (following radiotherapy), and trismus.…”
Section: Introductionmentioning
confidence: 99%
“…Noma can cause extensive soft tissue losses and trismus; excision of fibrosis and flap replacement are combined with a graded approach to maximize mouth opening, setting the basis for rational application of postoperative physiotherapy. 5 …”
Section: Introductionmentioning
confidence: 99%